The LGBTQ Movement and Islamic Perspectives: A Critical Analysis - Ahmad Fuzail Ibn Saeed; Dr. Nayab Gul; Huma Bukhari (Journal of Religion and Society, 2025)
The LGBTQ (Lesbian, Gay, Bisexual, Transgender, Queer) movement has emerged as a global socio-political and ideological phenomenon, advocating for redefined notions of human rights, sexual orientation, and gender identity. This research aims to critically analyse the foundations, objectives, and implications of the LGBTQ movement in light of Islamic teachings. The study explores the conceptual and legal framework of Islam concerning gender and sexuality, drawing upon the Qur'an, Sunnah, classical jurisprudence, and traditional Islamic values. Furthermore, it examines the ideological influence of Western liberal discourse on Muslim societies and assesses the intellectual and ethical challenges posed by such movements. The paper concludes with recommendations on how Muslim communities can respond to these challenges with wisdom, moderation, and adherence to Islamic ethical principles, while maintaining a constructive and principled engagement with global discourses. Keywords: LGBTQ, Islamic Perspectives, Gender Identity, Critical Analysis, Shariah, Social Movements, Muslim Societies